DIAGENESYS STAGE ANALYSIS OF SANDSTONE INTERVAL ON WELL DAR-24, GABUS FORMATION, ANOA FIELD, WEST NATUNA BASIN - Hanindya Ramadhani (KURVATEK, 2017)
Stage of diagenesis of a rock will effect the quality of the rock as a reservoir. Hence, it is a necessary to analyze the diagenesis stage of sandstone at Anoa Field, West Natuna Basin, since the diagenesis stage has not been identified properly. The analysis is carried out using thin section method in five different depths. The product of diagenesis is observed for its cementation level, compaction, recrystallization, dissolution, replacement, and type of porosity wich developed in the rock. The appearance of quartz overgrowth cement and pore filling and pore lining calcite cement show a diagenesis stage which are recrystallization and cementation. The appearance of bent mica mineral and suture grain contact can be a sign of late stage compaction. Dissolution of matrix, cement and grain in the sample show that the rock has come to mesodiagenesis stage. As a result of the observation, the conclusion can be made that the rock has passed the eodiagenesis and mesodigenesis phase. Porosity of the section is both primary porosity (interparticle) and secondary porosity (dissolved) with a range 15%-20% (medium to good). Crossplot depth vs porosity show a linear distribution, which when the depth is increase the porosity will decrease. So it can be concluded that the process of diagenesis is very influential on the quality of reservoir rocks in the study area.Keyword: Gabus Formation, sandstone diagenesis, stage of diagenesis.